2017
DOI: 10.1111/jgh.13674
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic therapies for severe steroid refractory hospitalized ulcerative colitis: A network meta‐analysis

Abstract: The results of the present comprehensive benefit-risk assessment using network meta-analysis provide RCT-based evidence on efficacy and safety of infliximab, cyclosporine, and tacrolimus for hospitalized patients with severe steroid refractory UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
0
8
0
4
Order By: Relevance
“…These results were opposed by a previous meta-analysis of observational studies, where IFX was associated with significantly higher rates of treatment response and a lower 12 months colectomy-rate compared to that with CYS (14). A lately reported network metaanalysis with benefit-risk analysis also suggested that there is a rank order of efficacy for colectomy-free rates favoring IFX over CYS, although the difference between the treatments was small (15).…”
Section: Objectives and Research Questionmentioning
confidence: 75%
“…These results were opposed by a previous meta-analysis of observational studies, where IFX was associated with significantly higher rates of treatment response and a lower 12 months colectomy-rate compared to that with CYS (14). A lately reported network metaanalysis with benefit-risk analysis also suggested that there is a rank order of efficacy for colectomy-free rates favoring IFX over CYS, although the difference between the treatments was small (15).…”
Section: Objectives and Research Questionmentioning
confidence: 75%
“…Aunque infliximab, adalimumab, golimumab y vedolizumab han sido aprobados por la Food and Drug Administration (FDA) y la European Medicine Agency (EMA) 16 , sólo infliximab ha sido sugerido en pacientes con CUg [2][3][4][5][6] . Por ello, es importante considerar la presencia de factores que pueden modificar la farmacocinética de infliximab y con ello los niveles plasmáticos y tisulares del fármaco [17][18][19] .…”
Section: Discussionunclassified
“…Aunque los corticoesteroides intravenosos han sido la principal estrategia, un tercio de los pacientes no responden a esta terapia 1 . Infliximab, ciclosporina y tacrolimus han sido utilizados como terapia de rescate disminuyendo la necesidad de colectomía precoz [2][3][4][5][6] . El actual esquema de inducción de infliximab en CUg está basado en los estudios ACT, los que excluyen a este grupo de pacientes 7 .…”
unclassified
“…The utility of Tac to treat steroid-refractory UC has been reported, with short-term response rates ranging from 55% to 98%, with less severe adverse events than CsA. [ 7 9 ] Therefore, Tac is now regarded as one of the main therapeutic options for steroid-refractory UC. Infliximab (IFX) is a TNFα antagonist, whose efficacy has been established in randomized controlled trials (RCTs).…”
Section: Introductionmentioning
confidence: 99%
“…Two recent meta-analyses did not reveal any significant differences between IFX and CsA in terms of colectomy and adverse events rates. [ 9 , 12 ] In Komaki et al's study, [ 9 ] a network meta-analysis was conducted to evaluate the efficacy of IFX, cyclosporine, and Tac for severe patients with UC, which suggested that IFX was somewhat superior to Tac and cyclosporine. This result was, however, conducted from indirect comparisons, and the number of studies in each meta-analysis was small ranging from 1 to 2, and it was not possible to conclude that IFX, Tac, and cyclosporine have comparable efficacy; therefore, the results from this meta-analysis should be interpreted with caution.…”
Section: Introductionmentioning
confidence: 99%